2018
DOI: 10.3892/ijo.2018.4351
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic anti-hepatoma effect of bufalin combined with sorafenib via mediating the tumor vascular microenvironment by targeting mTOR/VEGF signaling

Abstract: Sorafenib inhibits tumor growth primarily by inhibiting vessel formation, however, its efficacy requires improvement, therefore, the development of strategies which augment its antiangiogenic effect are of primary concern. Bufalin inhibits tumor cell proliferation and metastasis, and induces apoptosis. In our previous study, it was demonstrated that the antiangiogenic effect of sorafenib was improved by bufalin in human umbilical vein endothelial cells (HUVECs). However, whether bufalin synergizes with sorafen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…New agents or combinations of synergizing agents with differing or broader selectivity to inhibit a variety of angiogenic pathways, or targeting agents to specific populations with a sensitizing mutation may potentially overcome initial or acquired resistance to initial antiangiogenic inhibitor treatment. Some agents are already demonstrating encouraging results in the laboratory and clinic (13,36,43,(77)(78)(79).…”
Section: Future Directionsmentioning
confidence: 99%
“…New agents or combinations of synergizing agents with differing or broader selectivity to inhibit a variety of angiogenic pathways, or targeting agents to specific populations with a sensitizing mutation may potentially overcome initial or acquired resistance to initial antiangiogenic inhibitor treatment. Some agents are already demonstrating encouraging results in the laboratory and clinic (13,36,43,(77)(78)(79).…”
Section: Future Directionsmentioning
confidence: 99%
“…It not only provides oxygen and extra nutrient, maintains the high proliferation rate of cancer cells, but also promotes local and distant metastasis of malignant cells [62]. Bufalin had been reported to inhibit cancer cell migration and invasion in liver cancer and lung cancer cell lines by down-regulating vascular endothelial growth factor (VEGF), which plays a major role in tumor angiogenesis [46, 63, 64]. Anti-angiogenic drugs, such as Sorafenib, may be complicated by relatively easy-acquired drug resistance, rapid onset of relapse after discontinuation, and the potential for tumor metastasis.…”
Section: Molecular Mechanisms Of Anti-tumor Activitymentioning
confidence: 99%
“…A previous study revealed that Bufalin enhances the anti-angiogenic effect of Sorafenib via AKT/VEGF signaling [64]. The co-administration of Bufalin and Sorafenib provides a novel therapeutic option for patients with advanced HCC and is worthy for further in-depth investigations [63, 64].…”
Section: Molecular Mechanisms Of Anti-tumor Activitymentioning
confidence: 99%
“…International Publisher sorafenib has become the first-line treatment and made the long-term survival of patients possible to some extent. Even so, with the problems of disease progression, drug-resistance, and adverse drug reaction as the therapy progresses, the urgent need for a more potent novel, targeted drug to replace sorafenib remains an increasingly prominent issue [11][12][13][14][15].…”
Section: Ivyspringmentioning
confidence: 99%